THE EFFECTIVENESS OF ORAL PRESENTATION TECHNIQUE FOR SPEAKING SKILL TO STUDENTS AT SMA NEGERI 1 KOTAMOBAGU - Mellinia P Tawas; Sanerita Olii; Tirza A Kumayas (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
The purpose of this research is to reveal the students speaking skill by the use of the Oral Presentation Technique. This study is carried out on second-grade students at SMA Negeri 1 Kotamobagu during the academic year 2020/2021. A quantitative approach is used in this pre-experimental study. There are 22 students in one class for the subject. The experiment is divided into three stages: pre-test, treatment, and post-test. The instrument of the study is the oral test. The data are obtained by pre-test and post-test. Before giving the treatment, the researchers administer the pre-test to find out students’ speaking skill at the beginning. The post-test is conducted at the end after giving the treatment. In analyzing the obtained data, researchers use the mean score formula. The result shows that the average post-test score (4.09) is the highest of the pre-test score (2.59). This result may lead to a conclusion that the Oral Presentation Technique is effective for students' speaking skills in the second grade at SMA Negeri 1 Kotamobagu.